Mimesis: dalla riflessione teoretica alla prassi educativa - Gilberto Scaramuzzo (Firenze University Press, 2013)
The article reflects on Aristotle's Poetics, 4.1448 b4-19. It examines how the definition of man as a mimetic animal (b5-9) is underestimated in educational praxis, and then, according to Aristotle, points to mimesis as the core of the understanding/learning processes. Arguing a revaluation of mimesis as necessary to educational praxis, the article presents a project delivered through this principle in a multi-ethnic school context.